1997
DOI: 10.1007/s004210050298
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of techniques for measuring negative intramuscular pressures in humans

Abstract: Negative external pressure has been used previously in experiments on the blood circulation in humans and is currently being considered as a counter-measure to the musculoskeletal deconditioning which occurs during the exposure to microgravity. Intramuscular pressure (IMP) measurement is an important tool for determining the effectiveness of the transmission of negative pressure. Therefore two IMP techniques, a fibre optic transducer-tipped catheter and a fluid-filled teflon catheter with side holes, were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…3). In a recent paper a method for measuring negative intramuscular pressure similar to the one used in the present study was evaluated, and it was shown that the method was suited for recording negative pressures over a wide range (5). This is to our knowledge the first time changes in the interstitial pressure around the human Achilles tendon have been measured in relation to exercise.…”
Section: Discussionmentioning
confidence: 85%
“…3). In a recent paper a method for measuring negative intramuscular pressure similar to the one used in the present study was evaluated, and it was shown that the method was suited for recording negative pressures over a wide range (5). This is to our knowledge the first time changes in the interstitial pressure around the human Achilles tendon have been measured in relation to exercise.…”
Section: Discussionmentioning
confidence: 85%
“…Two studies have revealed that IMP in the resting state increased to approximately 6 mmHg at D2 37,38) , and two other studies have revealed that pressure from the outside approximately reflects IMP in muscle 40,41) . Therefore, it seems difficult to explain the augmentation in muscle mechanoreflex on the grounds of an ECC-induced increase in IMP and the vascular distension hypothesis (Fig.…”
Section: Respiratory Center 1-[2] Central Command (+) Baroreceptormentioning
confidence: 99%
“…It needs frequent zeroing and is often difficult to connect to trend monitoring. [23][24][25][26][27][28][29][30][34][35][36][37][38][39][40]42,[46][47][48][49] MTC ® (Microtransducer, Dräger Medical Electronics) is an electronic transducer and, therefore, there is no need for fluid infusion. This invasive pressure transducer consists of a small silicone chip with a very thin pressure-sensitive membrane, incorporated in a medical-grade housing.…”
Section: Introductionmentioning
confidence: 99%